Land grabbing, land rush, controle e estrangeirização da terra: Uma análise dos temas e tendências da produção acadêmica entre 2009 e 2017 - Pereira, Lorena Izá [UNESP] (My University, 2017)
Since 2008, the interest in the appropriation of land for agricultural production and/or speculation intensifies on a global scale. This process generated impacts in different spheres and the insertion of the land grabbing theme - in its different terms - in the research agendas was one of these. In this way, the objective is to analyze the academic production based on the intensification of land grabbing, identifying the main elements, debates, discourses and scales of analysis highlighted in the main research published on a global scale on the subject. In order to reach this objective, we applied as methodological procedure the survey and analysis of different formats of works that have as object of analysis the land grabbing and mapped the countries in which the institutions where the researches are developed are located and the countries that are the target of the surveys. There was a redirection in research agendas involving the rural world, in which we can identify two distinct phases in the scientific publications on land grabbing, which shows the evolution of the understanding of the same by the institutions, governments and academia. It was also possible to verify the existence of a research network, where the main node is the International Institute of Social Studies (ISS), of Erasmus University Rotterdam, in the Netherlands.
Land grabbing, land rush, land control and land foreignization: An analysis of the themes and trends of academic production between 2009 and 2017
Keywords: Academic production; Foreignization of land; Land control; Land grabbing